PENENTUAN JALUR DISTRIBUSI PADA TRAVELING SALESMAN PROBLEM (TSP) DENGAN ALGORITMA BRANCH AND BOUND DAN NEAREST NEIGHBOUR UNTUK MENGOPTIMALKAN BIAYA TRANSPORTASI DI UMKM BOLEN CRISPY MAK TIN - Muhammad Fadhel Ali; Alif Munazat; Muhammad Mirza Dwitama; Suseno Suseno (CV. ALIM'SPUBLISHING, 2025)
Optimizing distribution routes is an important step for MSMEs in increasing operational efficiency and customer satisfaction. This research was conducted on Bolen Crispy Mak Tin MSMEs which face distribution challenges with routes that are not yet optimal, causing increased transportation costs and the risk of decreasing product quality. This research uses the Branch and Bound and Nearest Neighbor algorithms to solve the Traveling Salesman Problem (TSP) problem in determining efficient distribution routes. The results of data processing are optimal routes that have the minimum distance with a total distance of 282.5 KM with route P-1-2-7-4-5-6-3-0 for the branch and Bound algorithm and 239 km with route P- 2-3-4-5-6-7-1-P for Nearest Neighbor This result is more optimal when compared to the previous route, namely P-1-2-3-4-5-6-7-P with a distance of 291 km analysis shows that Method Nearest Neighbor is able to provide an optimal solution by minimizing travel distance and distribution costs, while the Branch and Bound algorithm also provides an optimal solution but is less efficient. and distribution cost efficiency from Rp. 570,320.9 to 565,511.36 or 0.84% ​​more savings for the Branch and Bound Algorithm and 540,795.45 or 5.18% more savings for Nearest Neighbor